The Composition of Fish Catches in Purse Seiner Operating in the Indonesian Fisheries Management Area (WPP 713) Sulawesi Sea - Ritonga, Sarlandi; Perangin-angin, Robet; Prasetyono, Untung; Sugiono (Yayasan Serumpun Karang Konservasi, 2024)
Purse seine is a widely used fishing gear in Indonesia for capturing small schooling pelagic species. The study aimed to analyze the catch composition of purse seine fishing performed using the KM Bintang Mas Maritime based at Nusantara Fisheries Port (NFP) Pekalongan and fishing in Indonesia Fisheries Management Area (IFMA 713) Sulawesi Sea. Data was collected through fishing trips observations and catch documentation from September 12, 2023 to February 16, 2024. The total catch was 155,000 kg which was composed of three dominant target species: Decapterus macarellus (32.25%), D. punctatus (29.03%), and Sardinella lemuru (22.59%) which make up 83.87% of the total catch. Bycatch made up 16.13% and included Euthynnus affinis, Rastrelliger kanagurta, Selar crumenophthalmus, and Priacanthus macracanthus. The high proportions of small pelagic fish in the catch is indicative of purse seine selectivity and show the target stocks in IFMA 713 are available. This data highlights the significance of regular evaluation and dynamic management strategies that can adapt to evolving conditions to maintain ecological balance and enduring resources.